A Multidisciplinary Approach to Integrating Islamic Values and Local Culture into STEM Pedagogy in Arabic Language Learning - Sovia Fahraini; Muzakki Abdurrahman; Nada Ibrahim Alribdi; Muhammad Thohir; Moh Sholeh Afyuddin (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2026)
Arabic language learning has been dominated by traditional methods that emphasize memorization and analysis of classical texts, thus not supporting the development of 21st-century skills. This study aims to formulate an Arabic language learning model based on a multidisciplinary approach that integrates STEM, Islamic values, and local culture to create applicable, contextual, and meaningful learning experiences. The research method is a library research with a critical-analytical approach to the latest national and international literature, particularly those discussing STEM pedagogy, language learning, Islamic values-based education, and the local cultural context. The results of the study indicate that STEM integration allows Arabic to be used as a medium for exploration, discussion, and project production, while Islamic values ​​such as amanah (trust), adab, ta'āwun (respect), and ṣidq (compassion) serve as ethical guidelines in every activity. Local culture serves as a living and relevant context, strengthening motivation and meaning in learning. The proposed operational model emphasizes identification of real problems, linguistic exploration, cross-disciplinary integration, work production, and reflection and evaluation, in accordance with Vygotsky's principles of social constructivism. The contribution of this research is to present a holistic pedagogical framework that combines cognitive, affective, spiritual, and contextual aspects, so that Arabic language learning not only builds language competence, but also Islamic character, cultural awareness, and 21st-century skills that are relevant to global challenges.